PERAN PSIKOLOGI PERKEMBANGAN DALAM DUNIA PENDIDIKAN ANAK SMP - Sianturi, Novita Perdamean; Diarang, Ayudhia; Loho, Heskia; Rasjid, Aprilia (PT. Giat Konseling Nusantara, 2024)
This article discusses the importance of developmental psychology in the education of junior high school children, who are in the age range of 10 to 14 years old. Psychology, derived from the words